Validation and application of an evaluation questionnaire of the Pedagogical Project of the Nutrition Course of a public university in the perception of students, interns, preceptors and professor (Research, Society and Development, 2021)
This study aimed to validate an evaluation questionnaire of the Pedagogical Project of the Nutrition Course of a Brazilian public university in the perception of students, trainees, preceptors, and professors; apply this newly validated questionnaire; and analyze the results. The authors developed four assessment instruments using a Likert-type scale, with five dimensions: General competencies for student education; Teaching-learning process; Student evaluation; Contribution of the curricular component to professional training, and Interpersonal relationship between the internship team. In this study, the first two dimensions were applied to all respondents; the third dimension, except for preceptors; the fourth was used only to students and the last to interns and tutors. After the validation stage and the validated questionnaire applied, we obtained 569 responses: 464 from students, 34 from interns, 27 from tutors, and 47 professors. The dimensions evaluated showed a positive perception (average >3.00), except for the Dimension "Contribution of the discipline to professional training," considered the perception of attention for students (average 2.99). The five dimensions evaluated had gaps and aspects of being improved. However, the objectives of the course were met, and the evaluation showed that the methodological teaching procedures should be reviewed and renewed. We concluded that the study validated an instrument in terms of content and reliability in the perception of those involved and allowed for in-depth reflections on the student's general academic education competencies. These aspects allowed a global assessment and brought substantial subsidies for a pedagogical proposal for the studied course.